HP-β-CD-functionalized hydrogel SERS fingerprinting for rapid storage-year discrimination of white tea - Zhenglong Chen; Zhile Zhao; Yuxin Bu; Xinyan Yang; Yulin Fang; Hui Lin; Yudong Lu (Food Research International, 2026)

A pomegranate-inspired B@(NH4)2SiF6@LiClO4 architecture for spatiotemporally coordinated boron combustion - Jiayan Liang; Hongyu Zhang; Jian Zhang; Xuwen Wang; Yangming Wang; Hao Bai; Yi Rong; Kaifeng Lin; Debin Xia; Yulin Yang (Chemical Engineering Journal, 2026)

Construction of a rigid–flexible OVS/PHFA interphase on Al–Li alloy fuels for coupled stabilization and efficient energy release - Changsheng Tang; Shixiong Song; Luyang Wang; Pengxiang Li; Yanqiu Jiang; Yulin Yang; Debin Xia; Jian Zhang; Ping Wang; Kaifeng Lin (Chemical Engineering Journal, 2026)

Local oxophilicity Sm incorporation drives structural alteration of Cu2O/Cu catalyst in CO2 electroreduction - Zihao Wei; Yulin Qin; Mengbo Zou; Lin Jia; Haorun Li; Yuekun Zhang; Jinyu Wang; Zeyu Guo; Hao Wu; Zeyu Zhang; Shanghong Zeng (Journal of Environmental Chemical Engineering, 2026)

Enhanced aluminum removal via K+–NH4+ composite alum precipitation from beryllium leachates: Mechanism validation and application - Lin Yu; Xiaobo Min; Yunyan Wang; Yulin Zhou; Zhou Liao; Yun Li; Cong Peng; Hui Xu; Zhiyan Zeng; Yong Ke (Hydrometallurgy, 2026)

Curvature-regulated ion-electron coupling enables high-rate hard carbon anodes for sodium-ion batteries - Zeren Zhou; Yixiang Zhang; Yulin Ma; Qiaoyan Lin; Ye Ding; Lijun Yang; Lishuang Fan (Chemical Engineering Journal, 2026)

Harnessing white-light-emitting metal-organic frameworks for efficient and UV-stable perovskite solar cells - Wei Wang; Xingrui Zhang; Jian Zhang; Jiaqi Wang; Boyuan Hu; Yuhao Xiong; Kaifeng Lin; Debin Xia; Yulin Yang (Chemical Engineering Journal, 2026)

PTPRO Governs Synaptic Density, Long-Term Potentiation and Cognitive Function In Vivo - Xiangdong Wang; Jiaguo Wu; Mengna Liu; Kun Zhang; Xinping Yuan; Fangting Xing; Wenjie Xu; Yulin Zheng; Yifei Wu; Lin Luo; Xinyi Ding; Ge Gao; et al. (Neuroscience Bulletin, 2026)

Ammonium and heat stress reveal divergent life-history strategies and environmental resilience in coral-symbiont dinoflagellates - Yulin Huang; Shuaishuai Wu; Jiamin He; Shutao Wu; Zhen Shen; Yujie Wang; Ling Li; Senjie Lin (Coral Reefs, 2026)

An updated checklist of testate amoebae in China - Yangmin Qin; Yulin Zhu; Zixuan Lin; Daniel Puppe (Protist, 2026)

Phenotype-independent bioorthogonal capture system eliminates circulating tumor cells and tumor-derived exosomes in whole blood - Yangze Ji; Xiaojie Wang; Yulin Wang; Shaowen Zhou; Jiong Yang; Tianjiao Zhou; Yi Wang; Xian Wu Cheng; Lei Xing; Hu-Lin Jiang (Chemical Engineering Journal, 2026)

Nontargeted screening of carbonyl-containing hormonal residues in meat products for food safety by using intelligent high-resolution mass spectrometry-based workflow - Jiajin Yi; Yuan Wu; Dandan Zhang; Tian Lin; Shiquan Zhou; Caixia Yuan; Hairong Zhang; Chunyan Zhu; Liuxin Dong; Hanwen Bai; Yulin Hu; Alweali Yousif; et al. (Food Chemistry, 2026)

Machine learning for small-data in aquatic environments: a review of challenges, methods, and optimization approaches - Yulin Chen; Lin Liu; Dawen Gao (ENGINEERING Environment, 2026)

Improving growth performance across multiple sheep breeds by targeting the MSTN gene using an enhanced Cas12i system - Bo Liu; Huanyu Song; Miao Yan; Yu Wu; Pengfei Li; Zhanqing Fan; Yufei Chen; Yangsheng Wu; Jiapeng Lin; Liqin Wang; Xiaoyu Niu; Kun Xu; et al. (Science China Life Sciences, 2026)

A machine learning-based model for soil iron oxides estimation using fused hyperspectral and multispectral data - Yongshi Tan; Zhenxi Wei; Yan Xiao; Yulin Huang; Zongxin Li; Shuting Yang; Lin Zou; Lanhui Yang; Yusong Deng (Journal of Soils and Sediments, 2026)

Fuel–oxidizer integrated ionic liquid for electrically controlled solid propellants based on hydroxylammonium nitrate - Qiyang Wang; Haoyang Lu; Haoqi Guo; Boya Zhang; Ziyang Han; Jian Zhang; Debin Xia; Ping Wang; Yulin Yang; Kaifeng Lin (Chemical Engineering Journal, 2026)

WD-HRNN-BiGRU: A Novel Spatiotemporal Sequence Multi-Value Prediction Model - Zhongrong Zhang; Junyan Sun; Yulin Shen; Kang Lin; Yijia Liu; Jisheng Li (Water Resources Management, 2026)

Sewage sludge valorization into iron-carbon composites for environmental remediation: A critical review on synthesis, synergy, and sustainability - Haijie Ben; Yue Zhang; Huiming Zeng; Yulin Wang; Feng Lin; Zhikang Bao; Jian Zhang; Bingzhi Li; Jingxi Zhu; Meng Li; Yong Zeng; Chuan Liang; et al. (Bioresource Technology, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

Salvianolic acid A reduces lipotoxicity injury of cardiomyocytes by orchestrating oxidative stress and inflammation via Akt/Nrf2/NF-κB axis - Lin Li; Siqi Du; Xianghui Meng; Liding Bai; Danni Huang; Fengjie Zhou; Wenwen Li; Xianzhe Qiu; Yulin Qi; Yanyan Wang; Yao Chen; Yuhong Li (Journal of Molecular Histology, 2026)

Unlocking controllable ignition and combustion in onion-structured Al@Na3AlF6@AP composites through Na3AlF6 “Temperature Switch” - Xuwen Wang; Jian Zhang; Hao Bai; Changsheng Tang; Jiayan Liang; Zhe Shi; Kaifeng Lin; Debin Xia; Bowen Tao; Fang Du; Yulin Yang (Fuel, 2026)

Optimizing light and nitrogen distribution in maize-soybean intercropping systems to enhance crop yield - Zhen Fan; Binbin Qiang; Xinbo Zhang; Yanrong Lin; Yulin Wu; Xining Zhao; Enke Liu; Tie Cai; Peng Zhang; Tiening Liu; Xiaolong Ren; Xiaoli Chen (European Journal of Agronomy, 2026)

Large-scale analysis of SARS-CoV-2 genomic data from sewage using eVarEPS reveals that amino acid mutations detected in sewage provide an early warning on population prevalence - Ziquan Lv; Chang Shu; Yulin Fu; Yinghui Li; Shisong Fang; Xiangjie Yao; Qinglan Sun; Kesheng Peng; Jian Lu; Guomei Fan; Dongmei Liu; Jinzhen Tang; et al. (Water Research, 2025)

Investigation of the structure-activity relationship of resveratrol and its glycosylated and acylated derivatives in relation to their α-glucosidase inhibitory activities - Changdong Lin; Juyuan Luo; Shuo Wang; Cheng Shen; Shucan Zhang; Zhibo Song; Yumei Ma; Yongling Liu; Yulin Li; Tao Chen (Food Chemistry, 2025)

Effect of the CuxNi1-xN bimetallic electrocatalyst on the ignition and combustion of electrically controlled solid propellants - Ziyang Han; Qiyang Wang; Huimin Nai; Haoyang Lu; Yingxue Ju; Jian Zhang; Debin Xia; Yulin Yang; Kaifeng Lin (Chemical Engineering Journal, 2025)

Synthesis of SnO2-SnS2/SiO2 photonic-crystal-structure device for ultra-highly sensitive fluorescence sensing of NO2 - Yucong Xiong; Yanqiu Jiang; Lina Xie; Yinan Chen; Luyang Wang; Jian Zhang; Ping Wang; Debin Xia; Yulin Yang; Kaifeng Lin (Chemical Engineering Journal, 2025)

Low−temperature fabrication of highly reactive Al–Li alloy powders with enhanced HTPB compatibility and improved propellant combustion performance - Luyang Wang; Jiahe Li; Changsheng Tang; Pengxiang Li; Yulin Yang; Debin Xia; Jian Zhang; Ping Wang; Kaifeng Lin (Chemical Engineering Journal, 2025)

A novel Halo Tag-based photo-crosslinking system for efficient drug target identification via chemoproteomic profiling - Xing Liu; Wenjing Ji; Yulin Tao; Yuxiang Gong; Qiannan Zhang; Ruoyao Lin; Yang Yang; Yiting Wang; Shasha Li; Yu Zhang; Hongli Liu; Zhixiang Du; et al. (Analytica Chimica Acta, 2025)

Process and mechanism of low-temperature molten salt roasting conversion of beryl ore: Towards low-energy-consumption beryllium smelting - Lin Yu; Xiaobo Min; Hui Xu; Yunyan Wang; Yulin Zhou; Zhou Liao; Yun Li; Zhiyan Zeng; Yibin Xie; Cong Peng; Yong Ke (Journal of Environmental Chemical Engineering, 2025)

Pig bedding biochar enhances the Cd extraction capacity of Perilla frutescens by mitigating the toxicity of Cd-contaminated soil - Tianlian He; Xingyu Hao; Rui Jing; Zhenguo Li; Ying Chen; Mingwei Yang; Chengzhen Gu; Yulin Wang; Ruiyu Lin; Xinyu Zheng (Journal of Environmental Sciences, 2025)

Effect of 7-O-glycosyl acylation of flavonoids from barley seedlings on α-glucosidase inhibition - Tao Chen; Changdong Lin; Weihang Lu; Shuo Wang; Cheng Shen; Juyuan Luo; Yulin Li (Food Chemistry, 2025)

Facilitating extensive CC bond cleavage in lignin models through customized CeO2/C3N4 S-scheme heterojunction - Hongwu Liao; Chong Wang; Jiaxian Zheng; Zhuo Chen; Yulin Zhou; Chengning Ye; Xiangfeng Lin; Meng An; Yusuke Yamauchi; Yusuke Asakura; Zhanhui Yuan (Chemical Engineering Journal, 2025)

A strategy for enhancing mechanical properties of electrically controlled solid propellant via in-situ-induced microphase separation - Huimin Nai; Qiyang Wang; Yingxue Ju; Yangshun Ren; Jiahui Li; Jizeng Shang; Jian Zhang; Debin Xia; Ping Wang; Yulin Yang; Kaifeng Lin (Chemical Engineering Journal, 2025)

Multilevel surface enhancement of primary and secondary particles in cobalt-free high-nickel cathode material through Mo and W staged doping - Dandan Sun; Jiyuan Jian; Xin Zhang; Shuang Lin; Yixuan Qiao; Tao Wu; Xianhui Zhao; Rui Xiao; Ziwei Liu; Hua Huo; Pengjian Zuo; Yulin Ma; et al. (Chemical Engineering Journal, 2025)

Genomic Approaches to Enhance Disease Resistance in Large Yellow Croaker: Recent Progress and Future Perspectives - Zhou Jiang; Yulin Bai; Ning Li; Lin Chen; Ji Zhao; Yin Li; Tao Zhou; Peng Xu (Reviews in Aquaculture, 2025)
Large yellow croaker is an important marine aquaculture species in China, but frequent disease outbreaks have led to significant losses in the aquaculture industry. Although traditional genetic selection methods have long been applied in fish breeding, an increasing number of studies are introducing genomic selection methods into large yellow croaker breeding to target complex traits such as disease resistance. Recent advancements in genomic resources, including an updated reference genome and SNP array, have opened up new opportunities for genetic and evolutionary research on this species. This review provides an overview of the current status of the large yellow croaker aquaculture industry and the existing approaches to addressing disease challenges. It also summarizes genomic selection techniques, the genetic mechanisms underlying disease resistance traits, and potential improvements in genomic selection methods. Furthermore, we summarize future directions for large yellow croaker breeding, incorporating the application of genetic research, multi‐dimensional data integration, standardized testing protocols, and artificial intelligence for phenotypic measurement. These strategies have opened new pathways to enhance disease resistance in large yellow croaker and to promote the sustainable development of its aquaculture industry.

The response of crop yield, water and nitrogen use efficiency to organic fertilizer addition: A meta-analysis - Pengzhao Liu; Yanrong Lin; Xiantong Liu; Zhipeng Li; Zhen Fan; Zinan Yan; Yulin Wu; Xining Zhao; Xiaolong Ren; Xiaoli Chen (European Journal of Agronomy, 2025)

Preparation and combustion behavior of stabilized Al-Li compound fuel via mixing with ammonium perchlorate and metal oxides - Jiahe Li; Changsheng Tang; Luyang Wang; Yulin Yang; Debin Xia; Jian Zhang; Ping Wang; Kaifeng Lin (Chemical Engineering Journal, 2025)

UltraNet: Unleashing the Power of Simplicity for Accurate Medical Image Segmentation - Ziyi Han; Yuanyuan Zhang; Lin Liu; Yulin Zhang (Interdisciplinary Sciences: Computational Life Sciences, 2025)

Formation of halonitromethanes, dichloroacetonitrile, and trichloromethane in the presence of E. coli and nitrophenols during UV/post-chlorination - Tao Wang; Qian Tang; Lin Deng; Chaoqun Tan; Yulin Fu; Jun Hu; Rajendra Prasad Singh (Journal of Hazardous Materials, 2025)

Reducing cadmium uptake without compromising nitrogen uptake, photosynthesis, or yield in low-Cd hybrid rice - Meina Ji; Wen Ning; Lin Su; Zhi Wei; Dandan Shi; Yulin Liao; Xiang Ouyang; Baohua Fang; Bigang Mao; Shuoqi Chang (Field Crops Research, 2025)

Canagliflozin reverses doxorubicin-induced cardiotoxicity via restoration of autophagic homeostasis - Jianping Luo; Mingyuan He; Changzhu Liang; Xiaoxia Huang; Yingqi Zhu; Donghong Hu; Junyu Yan; Mingjue Li; Hairuo Lin; Wangjun Liao; Jianping Bin; Ziyun Guan; et al. (Toxicology and Applied Pharmacology, 2025)

Wound microenvironment sensing and self-adjusting hydrogel with glucose, ROS, and MMP-9 responsiveness for improving microcirculation of diabetes foot ulcers - Yang Yuan; Yulin Yang; Zhen Ji; Jingrong Feng; Lin Shu; Sa Xiao; Zhipeng Huang (Chemical Engineering Journal, 2025)

Exploring inhibition of Listeria monocytogenes biofilm by carvacrol based on action to quorum sensing - Xiaona Gao; Xinke Gao; Zichun Hua; Majid Alhomrani; Chao Shi; Lin Lin; Yulin Zhu (Food Bioscience, 2025)

Electrocatalytic oxidation for hydroxyl radicals generation: Exploring the role of an electrode-induced interphase on electronically controlled solid propellants - Bin Wang; Fuhan Liu; Huimin Nai; Haoqi Guo; Jian Zhang; Debin Xia; Kaifeng Lin; Yulin Yang (Chemical Engineering Journal, 2025)

Microneedle patch with pure drug tips for delivery of liraglutide: pharmacokinetics in rats and minipigs - Hongbing Lin; Jinbin Liu; Yulin Hou; Zhiyan Yu; Juan Hong; Jianghong Yu; Yu Chen; Jingwen Hu; Dengning Xia (Drug Delivery and Translational Research, 2025)

A review of liquid crystal monomers (LCMs) as emerging contaminants: Environmental occurrences, emissions, exposure routes and toxicity - Yulin Wang; Qianqian Jin; Huiju Lin; Xiaotong Xu; Kenneth M.Y. Leung; Kurunthachalam Kannan; Yuhe He (Journal of Hazardous Materials, 2024)

Heteronuclear FeN3-CuN3 atom pairs coordination engineering of single-atom catalysts for water splitting and Zn-Air batteries - Yinglin Zhang; Bo Yan; Chenchen Ji; Tingting Wei; Wenbin Niu; He Lin; Yulin Shi (Chemical Engineering Journal, 2024)

Phosphorus limitation intensifies heat-stress effects on the potential mutualistic capacity in the coral-derived Symbiodinium - Jiashun Li; Wenzhe Li; Yulin Huang; Hailu Bu; Kaidian Zhang; Senjie Lin (Science of The Total Environment, 2024)

Enhancing interfacial compatibility and ionic transportation kinetics in lithium-rich manganese oxide via magnetron sputtering conformal coating with amorphous LiPON - Yue Chen; Yulin Huang; Chenxi Fang; Pengcheng Wang; Houlin Cheng; Guiying Zhao; Yingbin Lin; Zhigao Huang; Jiaxin Li (Chemical Engineering Journal, 2024)

Quantitative trait locus analysis of gray leaf spot resistance in the maize IBM Syn10 DH population - Lina Cui; Mingfei Sun; Lin Zhang; Hongjie Zhu; Qianqian Kong; Ling Dong; Xianjun Liu; Xing Zeng; Yanjie Sun; Haiyan Zhang; Luyao Duan; Wenyi Li; et al. (Theoretical and Applied Genetics, 2024)

Proton-pumping rhodopsin of the coral symbiont Breviolum minutum and its potential role in coping with phosphorus deficiency in future warmer ocean - Minglei Ma; Yanchun You; Yulin Huang; Xueqiong Sun; Jiashun Li; Ling Li; Yujie Wang; Senjie Lin (Coral Reefs, 2024)

Cyclodextrin-based ternary supramolecular deep eutectic solvents for efficient extraction and analysis of trace quinolones and sulfonamides in wastewater by adjusting pH - Jingyu Zhang; Shang Li; Liping Yao; Yulin Han; Kexian Chen; Mingrong Qian; Zuguang Li; Hui Lin (Analytica Chimica Acta, 2024)

Design and development of dual-extruder food 3D printer based on selective compliance assembly robot arm and printing of various inks - Jingfu Pan; Xiaochen Chen; Yulin Zhu; Baoguo Xu; Changzhu Li; Myat Noe Khin; Haiying Cui; Lin Lin (Journal of Food Engineering, 2024)

High arsenic pollution of the eutrophic Lake Taihu and its relationship with iron, manganese, and dissolved organic matter: High-resolution synchronous analysis - Wenming Yan; Xiangyu He; Musong Chen; Bao Qian; Minjuan Li; Yulin Yan; Chen Lin; Zhigang Mao (Journal of Hazardous Materials, 2024)

Stability of a novel glycosylated peanut protein isolate delivery system loaded with gallic acid - Chenghui Zhang; Changzhu Li; Yulin Zhu; Haiying Cui; Lin Lin (Food Chemistry, 2024)

HLEL: A wetland classification algorithm with self-learning capability, taking the Sanjiang Nature Reserve I as an example - Wenhan Jiang; Meng Zhang; Jiangping Long; Yulin Pan; Yimin Ma; Hui Lin (Journal of Hydrology, 2023)

Transcriptional activation of membrane-related Toll-like receptor 5 through the NF-κB subunit p65 and Vibrio parahaemolyticus flagellin in orange-spotted grouper (Epinephelus coioides) - Xue Yu; Liangge He; Songze Gao; Yuqi Liu; Jiachang Xu; Yulin Zhao; Haoran Lin; Yong Zhang; Danqi Lu (Aquaculture, 2023)

Hydroxyl-groups engineering of triazole-based polymers for efficient photocatalytic hydrogen peroxide production - Feng Lin; Zhaoyang Ju; Yao Li; Jia Liu; Liyong Ding; Haijie Ben; Yulin Wang; Yuechao Wu; Ying Lei; Huiming Zeng; Shaohong Zang; Jun Chen; et al. (Journal of Cleaner Production, 2023)

Advancing hydrochar production and application: A critical examination of microwave irradiation and blended feedstocks synergy - Shaorong Du; Quan Zhang; Wangfang Ye; Zijing Wang; Zilin Liu; Jianhui Huang; Xin Xu; Yijing Wu; Xiaoyu Lin; Quan Sophia He; Sonil Nanda; Rahil Changotra; et al. (Journal of Cleaner Production, 2023)

Impact of COVID-19 pandemic on profiles of antibiotic-resistant genes and bacteria in hospital wastewater - Liang Zhao; Ziquan Lv; Liangqiang Lin; Xiaowei Li; Jian Xu; Suli Huang; Yuhua Chen; Yulin Fu; Changfeng Peng; Tingting Cao; Yuebin Ke; Xi Xia (Environmental Pollution, 2023)

Transcriptome analysis reveals important regulatory genes and pathways for tuber color variation in Pinellia ternata (Thunb.) Breit - Cong Yin; Ding Tang; Xiaoyu Liu; Zihan Li; Yulin Xiang; Kaiming Gao; Heyu Li; Lin Yuan; Bisheng Huang; Juan Li (Protoplasma, 2023)

Attention-aided semantic segmentation network for weed identification in pineapple field - Yulin Cai; Fanguo Zeng; Jiayi Xiao; WenJie Ai; Gaobi Kang; Yongda Lin; Zhuxuan Cai; Haowen Shi; Shuxin Zhong; Xuejun Yue (Computers and Electronics in Agriculture, 2023)

Response of soil erosion to vegetation restoration and terracing on the Loess Plateau - Peng Tian; Xiaojing Tian; Ren Geng; Guangju Zhao; Lin Yang; Xingmin Mu; Peng Gao; Wenyi Sun; Yulin Liu (CATENA, 2023)

Transcriptomics and physiological analyses unveil the distinct mechanisms of ATP and glucose-6-phosphate utilization in Phaeodactylum tricornutum - Xiaohua Zhang; Shuang Cheng; Zhengquan Gao; Yulin Cui; Qingshou Yao; Jiayang Qin; Xiangyong Liu; Senjie Lin (Frontiers in Marine Science, 2023)
Phosphoesters are a dominant component of marine dissolved organic phosphorus (DOP) and an important source of the phosphorus nutrient for phytoplankton, but the molecular mechanisms of their utilization by phytoplankton are divergent and poorly understood. In this study, we used the model diatom Phaeodactylum tricornutum to investigate and compare the utilization mechanisms of two different phosphoesters, adenosine triphosphate (ATP) and glucose-6-phosphate (G6P). We found that ATP and G6P can both be efficiently used to support the growth of P. tricornutum . Cells grown on ATP or G6P showed lower pigment contents and photosynthetic rates but higher cellular lipids relative to those grown on NaH 2 PO 4 (DIP). Surprisingly, in neither the ATP nor the G6P group were significant increases in whole-cell alkaline phosphatase (AP) activity detected, suggesting that utilization of both DOPs was not reliant on extracellular AP. Yet, ATP-grown cultures released DIP into the medium (i.e., ATP hydrolyzed extracellularly) whereas G6P-grown cultures did not. Furthermore, transcriptomic and RT-qPCR results showed that the gene encoding 5’ nucleotidase (5NT) in the ATP group and PhoD in the G6P group was upregulated. These results indicated that different pathways are involved in the use of these two DOPs, with ATP being hydrolyzed extracellularly likely by 5NT (PHATRDRAFT_44177) to release DIP for uptake, and G6P being directly absorbed and hydrolyzed intracellularly likely by PhoD (PHATRDRAFT_45757). Nevertheless, P. tricornutum under ATP and G6P conditions showed more similar transcriptomic profiles to each other than either compared to DIP-grown cultures, indicating similar metabolic functions of these two DOPs. These findings demonstrate that despite the high similarity in transcriptomic response to ATP and G6P conditions, the utilization mechanisms of these phosphoesters in the same species can be totally different, and the lack of AP activity does not necessarily signal the absence of DIP deficiency or the absence of DOP utilization.

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Capsule structured Al/FeF3/AP energetic microspheres with enhanced combustion performance and energy release efficiency by a microexplosion reaction - Xuwen Wang; Yinghui Hu; Jian Zhang; Jiayan Liang; Yulin Yang; Kaifeng Lin; Aimin Pang; Yong Shuai (Fuel, 2023)

Fabrication of polyamide thin film nanocomposite membranes with enhanced desalination performance modified by silica nanoparticles formed in-situ polymerization of tetramethoxysilane - Yunbo Tong; Yulin Wei; Han Zhang; Lin Wang; Lingling Li; Fangkun Xiao; Congjie Gao; Guiru Zhu (Journal of Environmental Chemical Engineering, 2023)

A rapid, high-throughput, and sensitive PEG-precipitation method for SARS-CoV-2 wastewater surveillance - Xiawan Zheng; Mengying Wang; Yu Deng; Xiaoqing Xu; Danxi Lin; Yulin Zhang; Shuxian Li; Jiahui Ding; Xianghui Shi; Chung In Yau; Leo L.M. Poon; Tong Zhang (Water Research, 2023)

Unique bacterial communities and lifestyles in deep ocean blue holes: Insights from the Yongle Blue Hole (South China Sea) - Shun Zhou; Jiwen Liu; Peng Yao; Liang Fu; Zuosheng Yang; Yulin Zhang; Rui Du; Chao Jia; Lin Chen; Jinchang Liang; Xiaolei Wang; Xiaochong Shi; et al. (Frontiers in Marine Science, 2023)
Deep ocean blue holes possess steep physicochemical gradients, especially low dissolved oxygen concentration, which shape the extraordinary microbial communities. However, the environmental responses of microorganisms with different lifestyles and knowledge of culturable microorganisms in the blue holes are still unknown. Here, we investigated the bacterial community structure with different lifestyles of the world’s deepest blue hole - the Yongle Blue Hole (YBH) in the South China Sea using both culture-dependent and -independent methods. YBH can be divided by oxygen content into an oxic zone, a suboxic zone and two anoxic zones. The abundance of bacteria, archaea, genes dsrB and soxB were all higher in the free-living (FL) lifestyle than in the particle-associated (PA) lifestyle, yet the diversity and richness of PA bacteria were higher than that of FL bacteria. More Gammaproteobacteria and less Alphaproteobacteria , Chloroflexi and Nitrospinae were observed within the FL fraction than within the PA fraction. The relative abundance of sulfur-oxidizing bacteria (SOB) was dominant between 100-140 m (anoxic zone I) in YBH, with a maximum of 90.0% (140 m FL fraction). The SOB in YBH were mainly colorless sulfur bacteria and purple non-sulfur bacteria, of which Thiomicrorhabdus and Sulfurimonas were the main representatives. In addition, a total of 294 bacterial strains were isolated on a variety of media and culture conditions, and 22.2% (18/81) of anaerobic strains were identified as potential novel species. Our study reveals a distinction between FL and PA bacteria in YBH. It contributes to further understanding of the bacterial community in deep ocean blue holes, and provides bacterial resources for subsequent studies on their adaptation to extreme marine environments.

Comparative transcriptome analysis of early sexual differentiation in the male and female gonads of common carp (Cyprinus carpio) - Mei Wang; Lin Chen; Zhixiong Zhou; Junzhu Xiao; Baohua Chen; Peihong Huang; Chengyu Li; Yaguo Xue; Ruoting Liu; Yulin Bai; Mengzhen Yan; Shuimu Hu; et al. (Aquaculture, 2023)

A combined study on Vallisneria spiralis and lanthanum modified bentonite to immobilize arsenic in sediments - Wenming Yan; Xiangyu He; Tingfeng Wu; Musong Chen; Juan Lin; Xiang Chen; Qi Li; Minjuan Li; Yulin Yan; Qi Yao (Environmental Research, 2023)

Research on Spatial Kinematics and Cutting Load Characteristics of TBM Disc Cutters - Kui Zhang; Yulin Zhang; Jie Liu; Laikuang Lin; Xuejun Zheng (Geotechnical and Geological Engineering, 2023)

A 2019 Outbreak Investigation of Hepatitis A Virus Infections in the United States Linked to Imported Fresh Blackberries - Monica McClure; Johnson Nsubuga; Martha P. Montgomery; Erin Jenkins; Alvin Crosby; Daniela Schoelen; Colin Basler; Sumathi Ramachandran; Yulin Lin; Guo-liang Xia; Yury Khudaykov; Vilasini Suktankar; et al. (Food and Environmental Virology, 2022)

The IRE1/JNK signaling pathway regulates inflammation cytokines and production of glomerular extracellular matrix in the acute kidney injury to chronic kidney disease transition - Yan Liang; Lingyun Qu; Zhenjie Liu; Lulu Liang; Yingzi Wang; Songxia Quan; Yulin Wang; Lin Tang (Molecular Biology Reports, 2022)

Mapping spatial-temporal nationwide soybean planting area in Argentina using Google Earth Engine - Yulin Shangguan; Xiyu Li; Yi Lin; Jinsong Deng; Le Yu (International Journal of Remote Sensing, 2022)

Identification and phylogenetic analysis of five Crataegus species (Rosaceae) based on complete chloroplast genomes - Liwei Wu; Yingxian Cui; Qing Wang; Zhichao Xu; Yu Wang; Yulin Lin; Jingyuan Song; Hui Yao (Planta, 2021)

MiR-124 and Small Molecules Synergistically Regulate the Generation of Neuronal Cells from Rat Cortical Reactive Astrocytes - Yangyang Zheng; Zhehao Huang; Jinying Xu; Kun Hou; Yifei Yu; Shuang Lv; Lin Chen; Yulin Li; Chengshi Quan; Guangfan Chi (Molecular Neurobiology, 2021)

Swine and rabbits are the main reservoirs of hepatitis E virus in China: detection of HEV RNA in feces of farmed and wild animals - Junke Xia; Hang Zeng; Lin Liu; Yulin Zhang; Peng Liu; Jiabao Geng; Lin Wang; Ling Wang; Hui Zhuang (Archives of Virology, 2015)

Increased osteogenesis in osteoporotic bone marrow stromal cells by overexpression of leptin - Baoyu Zheng; Jun Jiang; Kai Luo; Lingling Liu; Minkui Lin; Yulin Chen; Fuhua Yan (Cell and Tissue Research, 2015)

Discordant patterns of tissue-specific genetic characteristics in the HIV-1 env gene from HIV-associated neurocognitive disorder (HAND) and non-HAND patients - Yabo Ouyang; Lifeng Liu; Yulin Zhang; Lin Yuan; Zhiying Liu; Sufang Yang; Feili Wei; Luxin Qiao; Dexi Chen (Journal of NeuroVirology, 2014)

Detection of grass carp reovirus (GCRV) with monoclonal antibodies - Jing Hongli; Zhang Lifeng; Fang Zhenzhen; Xu Lipu; Zhang Min; Wang Na; Jiang Yulin; Lin Xiangmei (Archives of Virology, 2014)

Cloning and characterization of a novel diacylglycerol acyltransferase from the diatom Phaeodactylum tricornutum - Yulin Cui; Guoting Zheng; Xueqin Li; Hanzhi Lin; Peng Jiang; Song Qin (Journal of Applied Phycology, 2013)

Discordant genotypic resistance and HIV-1 genetic diversity from paired plasma and cerebrospinal fluid samples in Chinese settings - Lifeng Liu; Yulin Zhang; Feili Wei; Qingxia Zhao; Xicheng Wang; Lin Yuan; Ning Li; Dexi Chen (Journal of NeuroVirology, 2013)